Analyzing Subjective Defects in a Civil Tortious Lawsuit: Inconsistencies between Posita and Petitum in the Control Assumption of the Testator’s Estate (Case No. 415/Pdt.G/2022/PN.Jkt.Brt) - Azmi Ansyari; Syahwir Hafiz; Shabrina Harahap; Sufiarina Sufiarina (Unnes Law Journal, 2023)
Referring to a civil case number 415/Pdt.G/2022/PN.Jkt.Brt, the plaintiffs who are the testator’s wife and daughter file a Tortious lawsuit against the defendant for an unlawful act. The plaintiffs describe the unlawful act as taking control of the estate by the testator sibling who has a mutual agreement between the defendant and the testator’s wife. This has happened prior to the distribution of the estate among the rightful heirs. The panel of judges who have reviewed the case in question, give a verdict of ‘an inadmissible lawsuit claim.’ The point of interest that the writers want to bring up and research on is the reason behind judges’ verdict that has made the case as a “niet onvankelijke verklaard'' case. To elaborate further, doctrinal research is done on the principles of civil procedural law, especially the relationship between the type of civil litigation with its legal arguments (‘posita’) and the legal claims (‘petitum’). The research results show that there are major inconsistencies between the type of civil litigation that has been filed with the content of ‘posita’ and ‘petitium.’ The plaintiffs file a tortious lawsuit at the district court while their ‘posita’ are mixing between undistributed testator’s estate and the defendant’s action of taking over the estate that is based on an agreement. Besides that, the legal claims have a few mix-ups, including demanding to state a tortious act by the defendant, petitioning the court to invalidate the mutual agreement, and seeking the court’s determination of heirs. In a tortious lawsuit, the plaintiffs shall seek compensation for their losses. As an advocate, it is expected to have an awareness in preparing a good and proper legal argument and claims in a civil lawsuit. These inconsistencies yield an inadmissible lawsuit; hence the plaintiff’s legal interests cannot be served through civil legal proceedings.